Human papillomavirus vaccine uptake in South Korea - Jin Young Choi; Miseon Kim; Byung-Su Kwon; Su Jin Jeong; Dong Hoon Suh; Kidong Kim; Yong Beom Kim; Jae Hong No (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to assess the human papillomavirus (HPV) vaccine uptake rate in South Korean women and to identify factors affecting vaccination rate before initiation of the national HPV vaccination as a National Immunization Program (NIP) in Korea. Materials and methods: We conducted online survey in February 2016 with questions to 2000 women aged between 9 and 59 years in South Korea by distribution of age and region, to assess HPV uptake and associated correlates such as age, residential region, education, and socioeconomic status. Results: The overall HPV vaccine received at least 1 dose rate was 23.1%, and the highest rate of vaccination was observed in women aged 20–29 years (38.6%), followed by those aged 30–39 years (36.9%), 9–19 years (16.9%), 40–49 years (14.2%), and 50–59 years (12.5%). Factors affecting HPV vaccination included metropolitan cities (odds ratio [OR] = 1.44, 95% confidence interval [CI], 1.15–1.80), university graduate (OR = 1.45, 95% CI, 1.06–2.00), regular influenza vaccination (OR = 2.11, 95% CI, 1.64–2.70), visited clinic within the last 6 months (OR = 1.73, 95% CI, 1.20–2.51) and high family income (OR = 1.55, 95% CI, 1.01–2.37). Conclusion: HPV vaccine uptake is low in South Korean women. Correct publicity, education and economic support programs for HPV vaccine could play an important role in increasing HPV vaccine uptake in South Korea.